Logics of war explanations for limited and unlimited conflicts - Weisiger, Alex (Cornell studies in security affairs, 2013)
Alex Weisiger tests three explanations for a nation's decision to go to war and continue fighting regardless of the costs. He combines sharp statistical analysis of interstate wars over the past two centuries with nine narrative case studies.